PENGARUH LINGKUNGAN KERJA FISIK, STRES KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT. KIMIA FARMA, Tbk. SEMARANG - Putri, Sekar Widyasari; Rodhiyah, Rodhiyah; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Human resource performance has an important role in production because its impact the company profitability. Physical working environment, stress and discipline should be an important notice from the company because its impact the employee performance. PT. Kimia Farma, Tbk. is one of Indonesia State Owned Enterprise, wich focused on pharmacy-supplied business, and the production growth in past three years showed decline.The aim of this research is to understand the impact of physical working environment, stress and discipline towards production employmee. The type of the research is explanatory research. Interview use questionnaire and literature are a collecting data as a tool and 88 respondents. The data will analyze with statistic descriptive, simple and linar regression, correlation, determination and significant test. Result and disscusion, In partial physical working environment, and discipline give a positive and significant impact with, the relation in both variables is medium. Stress has a negative and significant impact. Discipline has positive and significant impact. Insimultaniously, physical working environtemt (X1) and discipline (X3) give a positive and significant impact and stress (X2) give a negative and significant impact trought performance (Y), the relation within those independent variables (X1,X2,X3) trought dependent variables (Y) are strong.The conclusion and suggestion, there are a significant impact between of physical work environment stress and discipline through performance. The suggestion company should pay more attention in physical working environment such as sanitation, descrease noise, and settle illumination in a working area also manage working stress in company, strive for working discipline by making regulation, giving a stict penalty and socialize it.